Service employees' acceptance of hotel front office systems : A test of technology acceptance model / Mohamad Abdullah Hemdi - Hemdi, Mohamad Abdullah (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2009)
Technology is gradually becoming a critical source of sustainable competitive advantages in the hospitality industry. In view of the benefits that IT provides to the hospitality industry, the extensive use of technology would appear to be an inevitable trend. However, despite the increasing use of technology in the hospitality industry, few studies have been conducted to investigate the relationship between the external variables and the technology acceptance model (TAM) framework to explain the acceptance behavior of hospitality organizations. This paper makes an attempt to investigate the relationship between information system quality, perceived ease of use, perceived usefulness, and attitude towards use by adopting an extended TAM. 240 frontline employees from twelve 5-star hotels in Penang, Malaysia participated in this study. Empirical findings indicate that the significance of all but two new variables. As a result, the study is able to find the acceptance of hotel front office systems (HFOSs) from the perspective of hotel frontline employees through the external variables of information system quality in order to enhance the model. Additionally, the paper presents theoretical and practical contributions for hotel managers and hotel information system (HIS) practitioners in order to increase frontlines acceptance of HFOS.